Writing of a aporia. Transits and obstructions in Existential Graphs of Charles S. Peirce - Tenorio, José Romero (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
The point of this article is to stress that graphs are a philosophical system which reflect upon the nature of writing. It is for this reason that we propose using the Spanish word «grafo» (comingfrom Spelling, writing and scripts) and not «graficos», a more mathematically oriented term. Rather than building up a symbolic or algebraic - like language, Peirce concentrates on the need of writing,and therefore thought, to expand its existence in their visible traces. System conventions and primary elements are discussed on this article. Firstly we deal with sections which organise expansion according to a logic of obstructions and openings, always respecting the continuous transit principle. Next, we enquire about the three elements of the system: the sheet of assertion, grapheus and graphist. Ending with a deep reflection on the ethics of creativity.
Keywords: Writing; continuous transits; book of sheets; bifurcations; aporia; hypostasis